2018
DOI: 10.7867/2317-5443.2017v5n2p111-136
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e acidentes de trabalho no meio rural de Santa Catarina

Abstract: O objetivo deste estudo foi calcular a correlação entre o grau de desenvolvimento rural e o número de acidentes em trabalho rural nas microrregiões de Chapecó, Concórdia e Xanxerê, no estado de Santa Catarina, no período de 2008 a 2013. Trata-se de um estudo exploratório, com abordagem quantitativa, e natureza aplicada. Para cada município, por meio da análise fatorial, elaborou-se o grau de desenvolvimento rural e, através da média aritmética simples, foi calculada a média de acidentes rurais. Com os dados de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
0
0
1
Order By: Relevance
“…In the present study, we observed a prevalence of 16.4% in the occurrence of occupational accidents. This phenomenon was also reported in the Southern region, where there was also a correlation between the occurrence of occupational accidents and health conditions (19) . In the Southeast region, there was an occurrence of occupational accidents resulting from the agricultural machinery handling (20) , as well as pesticide handling in the Northeast region (9) .…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, we observed a prevalence of 16.4% in the occurrence of occupational accidents. This phenomenon was also reported in the Southern region, where there was also a correlation between the occurrence of occupational accidents and health conditions (19) . In the Southeast region, there was an occurrence of occupational accidents resulting from the agricultural machinery handling (20) , as well as pesticide handling in the Northeast region (9) .…”
Section: Discussionsupporting
confidence: 65%
“…No presente estudo, observou-se a prevalência de 16,4% na ocorrência de acidente no trabalho. Esse fenômeno também foi relatado na região Sul, em que também houve correlação entre a ocorrência de acidentes de trabalho e as condições de saúde (19) . Na região Sudeste, verificou-se ocorrência de acidentes no trabalho decorrente da manipulação de maquinários agrícolas (20) , assim como da manipulação de agrotóxicos na região Nordeste (9) .…”
Section: Discussionunclassified